Development performance and stagflation - Ghosh, Santikumar (Calcutta : World Press, 1974)
This book attempts to analyse broadly the course of economic development pursued by India during the Five Year Plans. It examines the nature and extent of the structural transformation that has taken place.
Includes index.
Bibliography: p. [57]-58.
usc 21/06/18
Loans
Keywords: Economic development; Economic policy; Inflation (Finance); India